The duke gets even - Shupe, Joanna (Shupe, Joanna. Fifth Avenue rebels, 2023)
To escape the shackles of marriage, Nellie Young purposely ruined her reputation a long time ago. Now she dedicates herself to hedonistic pleasures only, like kissing a handsome stranger in the ocean under the moonlight... To save his estate, the proper Duke of Lockwood must marry the perfect bride--wealthy, with an unblemished reputation. While in New York he's the perfect gentleman, and no one knows he's suppressing his darkest desires. The last thing he needs is another scandal. Except Nellie sees through Lockwood's charade, straight to the real man underneath. This uptight duke is far more than he lets on, and she can't resist him. Their secret affair turns scorching, far more than either expected. And when his beautiful rebel finds an unconventional cause, Lockwood has to decide if he's willing to sacrifice everything to keep her.